International Perspectives on the Role of Indigenous Fathers in Caring for Their Infants: A Scoping Study - Wright, Amy L.; VanEvery, Rachel; Johnson, David; Martin, Landon; McGall, Clare; Cano, Jennifer K.; Burnside, Heather (The International Indigenous Policy Journal, 2022)
Effective early childhood development interventions require a thorough understanding parental roles in supporting their infants’ health. Yet, the role of Indigenous fathers is not well illustrated within the literature. This scoping study synthesizes the roles that Indigenous fathers have in promoting the health and development of their infants, using an international perspective. Findings support future research to develop effective early childhood parenting interventions that address the unique needs of Indigenous fathers. Methods Scoping methodology was undertaken with inclusion criteria stipulating infants less than two years of age, and describing the role of Indigenous fathers (or father figures) in meeting the health and/or developmental needs of their infants. Descriptive and pattern coding were used during data extraction and synthesis. Collaboration with Indigenous community partners, including First Nations fathers, promoted ethical research conduct and findings framed within Indigenous ways of knowing. Results Findings highlight a journey to becoming a father, beginning with assuming a new identity as a father, establishing their fathering role, and supporting one another throughout the journey. This process has significant implications for a child’s development and wellbeing and related health policy. Conclusions This review synthesizes the experiences of Indigenous fathers across the globe, and while the journey is not fully understood, these initial findings are helpful to support future research and health policy. It is in the best interests of children if men are proactively supported in their transition to fatherhood as early as possible to promote a positive impact on their children’s development and future wellbeing.